The Samothrace Lidar Project (SaLiP) - Matsas, Dimitris; Wescoat, Bonna D.; Witmore, Christopher L.; Page, Michael; Garrison, Thomas G.; Manquen, Brody W. (Journal of Greek Archaeology, 2025)
This article reports on the Samothrace Lidar Project (SaLiP), a research collaboration in conjunction with the American Excavations Samothrace and as part of the Samothrace Exploration Project. SaLiP seeks to shed light on occupation and land use on the forested, mountainous island of Samothrace in the northeastern Aegean from just before its earliest human inhabitation to the present. As a wholeisland investigation, our research collaboration has four primary aims: (1) to investigate the seeming void of the Late Bronze Age, a period of complex and varied patterns of transformation and transition across the regions of the northern Aegean, eastern Balkan Peninsula, and northwestern Anatolia; (2) to document the agricultural landscape which is rich in agrarian ruins, distinctive water management networks, and water-driven pre-and proto-industrial installations; (3) to locate anthropogenic features currently obscured by vegetation in wooded understories across the island; and, (4) to gain a better understanding of the landscape generally, given its rapidly changing geomorphology. During the summer of 2023 we commissioned AeroPhoto Co Ltd of Thessaloniki to undertake the airborne laser scanning of the three most important zones of diachronic human activity on Samothrace.